LQ control design for the containment of the HIV/AIDS diffusion - Di Giamberardino, Paolo; Iacoviello, Daniela (Control engineering practice, 2018)
An optimal control design approach is applied to a novel HIV/AIDS model to reduce the infection diffusion. Two classes of susceptible subjects, the wise one and the incautious ones, and three classes of infectious subjects, the ones not aware of their condition and the subjects in the pre-aids or in the aids status, are considered. The control input, represented by information campaigns and the medication action, is designed by means of a linear quadratic approach on the linearized model. Moreover, a preliminary state observer for the unmeasurable number of the unconscious infectious subjects is introduced. Numerical results show the effectiveness of the solution, and its robustness with respect to the approximations introduced by the linearization. •An optimal control approach is applied to an HIV/AIDS model to reduce its diffusion.•The number of infectious subjects unaware of their status is minimized.•This number is not available, and a state observer is required.•The aim is to determine a feedback control law.•The separation principle is applied on the suitably linearized system.